Comparison of Digital Chest Radiography to Purified Protein Derivative for Screening of Tuberculosis in Newly Admitted Inmates. (October 2016) - Degner, Nicholas R.; Joshua, Alfred; Padilla, Rex; Vo, Holly H.; Vilke, Gary M.
This study compares purified protein derivative (PPD) screening to digital chest radiography (CXR) screening for tuberculosis (TB) in newly admitted inmates in the San Diego County Jail system. The study period lasted from 2002 to 2014, during which 45 cases of active TB were detected, a rate of 69.2 cases per 100, 000 person-years. Compared to PPD, CXR reduces the median number of days active TB cases were in the general population from 44.4 to 5.2 days and the number of exposures from 1, 222 to 138 persons. These results confirm that CXR remains a more effective method for preventing exposure to active TB in jail facilities.